THE DIVERSITY OF TERRESTRIAL ARACEAE IN MT. WATUWILA COMPLEX, SOUTH-EAST OF SULAWESI - Ina Erlinawati (The East Java Biological Society, 2010)
The arums comprise the family of Araceae, including the numerous aroids subfamily, monocotyledonous flowering plants, in which flowers are borne on a type of inflorescence called a spadix. The diversity of terrestrial Araceae in Sulawesi is very poorly documented and understood and remains critically threatened. The aims of this study were to understand the diversity of terrestrial Araceae on Mount Watuwila Complex and to add the number specimen collection in Herbarium Bogoriense. The exploration was conducted by used exploring method, including collection, identification and description. The exploration on Mount Watuwila Complex (170–800 m alt.), May 7–29, 2008 was got 22 number collections of Araceae, consist of 12 numbers of terrestrial Araceae, 10 species, those are Aglaonema simplex Bl., Alocasia macrorrhizos (L.) G. Don, Alocasia suhirmaniana Yuzammi & A. Hay, Colocasia esculenta (L.) Schott, Homalomena spp. (3 species), Schismatoglottis calyptrata (Roxb.) Zoll. & Moritzi, S. plurivenia Alderw and Spathiphyllum commutatum Schott. Schismatoglottis calyptrata (Roxb.) Zoll. & Moritzi is dominant species and Alocasia suhirmaniana Yuzammi & A. Hay is endemic species. The descriptions of each species were made.